Early Islamic Spain the History of Ibn al-Qūṭīya : a study of the unique Arabic manuscript in the Bibliothèque Nationale de France, Paris, with a translation, notes, and comments - Ibn al-Qūṭīyah, Muḥammad ibn ʻUmar, -977. (Culture and civilisation in the Middle East., 2009)
Including maps, an extensive introduction and notes and commentary by the translator, Islamic Spain is the first English language translation of the important history of Islamic Spain by Ibn al-Qutiyyah, one of the earliest and significant histories of Muslim Spain and an important source for scholars.